AI and the Cognitive Reshaping of Consumers: A Paradigm Shift in Marketing and Advertising - Masoud Lajevardi (International Journal of Business and Quality Research, 2025)
Artificial Intelligence (AI) has long been viewed as a tool to enhance marketing efficiency. However, we are now entering a deeper, less explored phase of the AI-marketing relationship — one that directly affects consumer cognition, autonomy, and identity. This article offers a perspective on how AI technologies are not just influencing behavior but are actively reshaping the cognitive architecture of consumers. In doing so, AI is contributing to a paradigm shift in advertising and marketing — moving from reactive persuasion to predictive and pre-emptive influence. This shift requires a reevaluation of key assumptions in marketing theory, particularly regarding choice, agency, and ethical responsibility.